STRATEGI PENGEMBANGAN SISTEM INFORMASI PELAYANAN KANTOR KELURAHAN MENGGUNAKAN ANALISIS SWOT - Fitri Khoirunnisa; Siti Roifah; Soni Setiawan; Maxsi Ary (Universitas Islam Kuantan Singingi, 2020)
Electronic-based Government System (SPBE) is the government's effort in developing an electronic-based government organization, so that there is an increase in the quality of public services. The system that runs in Sukabungah which is still manual and the lack of providing information to the community related to village services is an obstacle in improving the quality of the organization. Therefore the use of organizational development strategy analysis is very necessary for the Sukabungah village office to achieve maximum organizational strategy. In this study the method used in improving the quality of service is the SWOT analysis, which is used to develop the potential of the organization and to find out internal and external factors of the organization. In the SWOT analysis that has been carried out on Sukabungah village office it can be seen that Sukabungah village office is included in the quadrant I strategy which means supporting an aggressive strategy, therefore in developing an organization that will be achieved has a huge opportunity, so this can be a good development for Sukabungah sub-district. Implementation in the development of this SWOT analysis is by designing a village service information system where this system will assist the government in improving the Electronic-Based Government System (SPBE) as well as assisting the urban village in improving the quality of the organization and facilitating the existing service system.